Response of wheat to soil application of nitrogen and sulphur - Fageria, Nand Kumar; Singh, Hargayan (Pesquisa Agropecuaria Brasileira, 2014)
A pot experiment was conducted with clay loam alkaline (calcarous) soil from the University of Udaipur Agronomy farm in Rajasthan, India to determine the effects of varying nitrogen and sulphur applications on two wheat varieties at different stages of growth. One hundred kg/ha of nitrogen and 150 to 225 kg/ha of sulphur were found to be the optimum doses under all growth stages. Variety V1 (HD 2009 - Triticum aestivum) was found to be superior to V2 (HD 4519 – Triticum durum) on all characters studied, including chemical composition, with the exception of test weight. Total nitrogen and sulphur accumulation in the plant increased almost linearly until maturity. Thus, in a fertilization program it would be important to have an adequate supply of nitrogen and sulphur throughout the growing season. Application of nitrogen resulted in increased plant levels of phosphorus, calcium and sulphur. Sulphur application did not affect plant levels of calcium and phosphorus; however, nitrogen content did increase as sulphur application increased. In order to support satisfactory plant growth and development, the soil used in this study must be able to supply at least 1.5 to 4 mg of nitrogen per plant per week within the growth period of 55 to 135 days, and 1.3 to 3.5 mg of sulphur per plant per week during the same period.